Diagnosis and treatment of liver metastases of parathyroid carcinoma - Su, Chaoyun; Zhang, Junwei; Yang, Huayu; Xu, Yiyao; Lu, Xin (Frontiers in Endocrinology, 2022)
Introduction Parathyroid carcinoma (PC) is a very rare endocrine malignancy occurring in less than 1% of all cases of primary hyperparathyroidism (pHPT). The liver is the second most common target organ for distant metastases of PC, but no guidelines are available for the diagnosis and treatment of liver metastases. In this study, we attempted to summarize the characteristics of the diagnosis and treatment of liver metastases based on our patients and other cases reported in the literature. Materials and methods The files of all patients diagnosed with PC with liver metastases summarized at our center between 2000 and 2022 were reviewed, and three datasets from Medline, Web of Science, and Embase were systematically searched to identify relevant articles. Results Three patients with liver metastases from our center and 11 patients from the literature were included in the study. All patients had pHPT with borderline remission of hypercalcemia after each operation. A total of 71.4% of the patients’ liver lesions were found by abdominal CT scans, while 35.7% were found by MRI, PET-CT, and fine-needle aspiration biopsy (FNAB), which were also helpful for diagnosis. Eight of nine patients (88.9%) who underwent surgery, radiofrequency ablation (RFA), or transcatheter arterial embolization (TAE) were alive, and only one postoperative patient died after a follow-up of 60 months. Conclusions PC is a rare malignant tumor prone to recurrence and metastasis, and postoperative reviews should be carried out routinely. Abnormally elevated parathyroid hormone (PTH) and serum calcium can indicate recurrence or metastasis. Enhanced CT and MRI can provide valuable support for the diagnosis of liver metastases, but whether [18F]FDG-PET-CT, [18F]FCH-PET-CT, or [11C]choline-PET-CT can be used as a diagnostic basis requires further study. Resection of liver metastases, segmental hepatectomy, or RFA can significantly improve patients’ symptoms.